ENTREPRENEURIAL MINDSET: THE KEY TO SUCCESS IN THE BUSINESS WORLD - Amra Ulvita Azhiin; Dendy Tirtoadisuryo; Stevianus Arief; Juniarto Dwi Utomo; Kasmin Kasmin (CV. Adiba Aisha Amira, 2025)
This Entrepreneurial Mindset: The Key to Success in the Business World discusses the importance of an entrepreneurial mindset as a main element in achieving success in the competitive business world. This research identifies how entrepreneurs who have a strong entrepreneurial mindset can be more effective in managing risk, innovating, and facing the inevitable challenges in their business journey. This study adopts a qualitative approach using in-depth interviews, focus group discussions (FGD), and participant observation to explore the direct experiences of successful entrepreneurs and executives of large companies. The research results show that an entrepreneurial mindset is not only related to creativity and innovation, but also to intelligent decision making, mental resilience in the face of failure, and the ability to see opportunities amidst uncertainty. This research also highlights how this mindset is applied in various business contexts, both in small and large companies. It was found that entrepreneurs who have a strong entrepreneurial mindset tend to be more adaptive to market changes, braver to take risks, and more creative in finding solutions to the problems they face. Thus, this research concludes that having a positive and strong entrepreneurial mindset is a key factor in achieving business success.